Phenolic Content and Antioxidant Activity during the Development of Brookfield' and Mishima' Apples - Stanger M.C.* (2017)
© 2017 American Chemical Society.The aim of this study was to characterize the changes in the contents of total (TPC) and individual (IPC) phenolic compounds, the total antioxidant activity (TAA) in the peel and pulp, and total anthocyanins (TAN) in the peel during the development of the fruits of Brookfield' and Mishima' apple trees. Brookfield' apples were harvested from the 49th to the 138th days after full bloom (DAFB) and Mishima' apples from the 45th to the 172th DAFB. In the pulp, the IPC, TPC, and TAA rapidly reduced at 75 and 79 DAFB for the Brookfield' and Mishima' apples, respectively, and then remained constant until commercial maturity. In the peel of Brookfield' apples there was a reduction in the TPC and TAA at 79 DAFB. The quercetin 3-galactoside, epicatechin, and procyanidin B2 contents reduced up to 107 DAFB with a subsequent increase in the values at commercial maturity. In the peel of Mishima' apples there was a reduction in the TPC, TAA, epicatechin, and procyanidin B1 and B2 contents at 130 DAFB, with a subsequent increase until commercial maturity. The TAN content in the peel increased during the 2 and 4 weeks prior to commercial maturity for Brookfield' and Mishima' apples, respectively. In the pulp and peel of both cultivars there was a reduction in the IPC, TPC, and TAA as the development proceeded. On nearing commercial maturity, there was an increase in the contents of quercetin 3-galactoside, epicatechin, procyanidin B2, and TAN in the peel for both cultivars.